Estudo da qualidade de furos sedes de rolamentos produzidos em peças de liga de alumínio por mandrilamento com ferramenta de PCD - Paulo Paiva de Carvalho (2017)
The application technologies of machining techniques with MQL (minimal quantity of liquid), Wet machining and Dry machining have been studied extensively in several applications, operations and different materials, mainly the machining with MQL, that combines better of both machining (Wet and Dry) once it reduces the environmental impacts and cost of the product, both due the reduction of the cutting fluid consumption from process. Machining of aluminum parts requires special attention due to the higher probability of BUE (built-up edge) formation and deformations caused by the cutting temperature. This may prevent the application of machining techniques with MQL and Dry, especially in the finishing operations, which define the final qualitative characteristics of the products. This paper aims to evaluate the performance of machining techniques with MQL, Cutting Fluid and Dry machining through the study of the qualitative characteristics diameter and roundness, in seat bearing holes of manufactured aluminum parts in the reaming operation using PCD tool. The experiments were designed with DOE (Design Of Experiments) and analysis of variance (ANOVA, whose cutting parameters, cutting speed (842 and 1263 m/min), feed rate (0.15 and 0.30 mm/rev) and depth of cut (0.4 and 0.65 mm) were selected as input variables, using the full factorial. The diameter and roundness were defined as output variables to the evaluation of the hole quality. The results showed a superior performance of MQL in relation to and Wet machining even considering the restrictions of the external application of MQL. Dry machining has presented values above the specified tolerances for both diameter and roundness, not being recommended for reaming machining of the aluminum alloy. In general, cutting speed and feed rate were the main linear parameters of influence, while depth of cut and feed rate were the main combined influences on diameter and roundness